ANALISIS PERILAKU PENGGUNA KART KREDIT BANK SYARIAH - Ainun Mardiah Napitupulu (Adpertens: Jurnal Ekonomi dan Manajemen, 2024)
Today the types of credit cards are increasingly diverse. Issuance of this credit card is not only done by conventional banks but has also been issued by Islamic banks after the issuance of the DSN-MUI No.54 / DSN-MUI / X / 2006 fatwa concerning the Sharia Card, which has stated regarding the permissibility of Islamic credit cards. The purpose of this study is to analyze customer / consumer behavior in using the Sharia Card, namely how the consumer / customer behavior in using the Sharia Card. The approach in this research is a qualitative approach using descriptive qualitative analysis and the indicators made as the basis are the indicators of Tawazun and Israf. Based on the data analysis that has been carried out on customer / consumer behavior in using the Syariah Card / iB Hasanah Card, the results show that customers tend to be tawazun / balanced in using the Syariah Card / iB Hasanah Card.